Top-Down Characterization of an Antimicrobial Sanitizer, Leading From Quenchers of Efficacy to Mode of Action - Wohlgemuth, Franziska; Gomes, Rachel L.; Singleton, Ian; Rawson, Frankie J.; Avery, Simon V. (Frontiers in Microbiology, 2020)
We developed a top-down strategy to characterize an antimicrobial, oxidizing sanitizer, which has diverse proposed applications including surface-sanitization of fresh foods, and with benefits for water resilience. The strategy involved finding quenchers of antimicrobial activity then antimicrobial mode of action, by identifying key chemical reaction partners starting from complex matrices, narrowing down reactivity to specific organic molecules within cells. The sanitizer electrolyzed-water (EW) retained partial fungicidal activity against the food-spoilage fungus Aspergillus niger at high levels of added soils (30–750 mg mL–1), commonly associated with harvested produce. Soil with high organic load (98 mg g–1) gave stronger EW inactivation. Marked inactivation by a complex organics mix (YEPD medium) was linked to its protein-rich components. Addition of pure proteins or amino acids (≤1 mg mL–1) fully suppressed EW activity. Mechanism was interrogated further with the yeast model, corroborating marked suppression of EW action by the amino acid methionine. Pre-culture with methionine increased resistance to EW, sodium hypochlorite, or chlorine-free ozonated water. Overexpression of methionine sulfoxide reductases (which reduce oxidized methionine) protected against EW. Fluoroprobe-based analyses indicated that methionine and cysteine inactivate free chlorine species in EW. Intracellular methionine oxidation can disturb cellular FeS-clusters and we showed that EW treatment impairs FeS-enzyme activity. The study establishes the value of a top-down approach for multi-level characterization of sanitizer efficacy and action. The results reveal proteins and amino acids as key quenchers of EW activity and, among the amino acids, the importance of methionine oxidation and FeS-cluster damage for antimicrobial mode-of-action.